2017
DOI: 10.1002/smtd.201700167
|View full text |Cite
|
Sign up to set email alerts
|

3D Space-Confined Pyrolysis of Double-Network Aerogels Containing In-Fe Cyanogel and Polyaniline: A New Approach to Hierarchically Porous Carbon with Exclusive Fe-N x Active Sites for Oxygen Reduction Catalysis

Abstract: Iron and nitrogen co‐doped carbon (Fe–N/C) nanomaterials are promising non‐Pt catalysts toward the oxygen reduction reaction (ORR). Both spectroscopy and density functional theory studies reveal that Fe–Nx accounts for the ORR activity. However, Fe–N/C catalysts prepared by traditional high‐temperature pyrolysis always contain less active Fe or Fe3C nanoparticles, and it remains a great challenge to obtain Fe–N/C catalysts with high‐content Fe–Nx active sites. Herein, a 3D space‐confined strategy for the pyrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…The increasing intensity suggests the enhanced graphitic degree with increasing pyrolysis temperature, which would improve the electronic conductivity of carbon skeleton. X‐ray photoelectron spectroscopy (XPS) was utilized to analyze the chemical composition of NPC samples . The survey XPS of samples (Figure b and S3) exhibit the presence of carbon, nitrogen, and the adsorbed oxygen, which is in good agreement with the elemental mapping analysis.…”
Section: Resultssupporting
confidence: 67%
“…The increasing intensity suggests the enhanced graphitic degree with increasing pyrolysis temperature, which would improve the electronic conductivity of carbon skeleton. X‐ray photoelectron spectroscopy (XPS) was utilized to analyze the chemical composition of NPC samples . The survey XPS of samples (Figure b and S3) exhibit the presence of carbon, nitrogen, and the adsorbed oxygen, which is in good agreement with the elemental mapping analysis.…”
Section: Resultssupporting
confidence: 67%
“…In which, metal‐nitrogen‐carbon (M−N−C, M=Fe, Co, etc) catalysts were considered as the most promising ORR electrocatalysts, and have attracted the most enormous interest of researchers in the past few years . Previous research revealed that the ideal ORR performance of M−N−C catalysts contributed to the exclusive active sites of surface nitrogen assorted with metal ,. What's more, the ORR activity of M−N−C catalysts were also influenced by carbon source, nitrogen source, the type of metal salt and the pyrolysis temperature, etc .…”
Section: Strategies Of Improving the Orr Catalytic Activitymentioning
confidence: 99%
“…[45] This result implied that the D3 site in Fe-N-HPC was probablyt ransformed into D1 and D2 sites for Fe-N-HPC-A during the acid-washing process. Althoughi ntensivei nvestigations have shown that post-treatment (i.e.,t he acid-washing and second heat-treatment)c an lead to an improvement of ORR activity, [46][47][48] the original reasonf or the enhanced activity is still ambiguous. [20] It may explaint he slightly inferior or almostu nchanged ORRa ctivity for Fe-N-HPC-A as compared with Fe-N-HPC.…”
Section: Active Site Formationo Ff E-n-hpc-ahe Lectrocatalystmentioning
confidence: 99%
“…[12,21] Besides, no obvious peak corresponding to the Fe-based crystalline phases( e.g.,F ea nd Fe 3 C) and less-activeD 2s ite were detected, suggesting the predominant presenceo fa ctive D1 andD 3s ites for Fe-N-HPC-AH. Althoughi ntensivei nvestigations have shown that post-treatment (i.e.,t he acid-washing and second heat-treatment)c an lead to an improvement of ORR activity, [46][47][48] the original reasonf or the enhanced activity is still ambiguous. In this work, we speculate that the significantly improved ORR activity is primarily attributed to the atomic-levelr econstruction of Fe-N 4 moieties with formation of absolutep resence D1 and D3 sites, inducedb ythe acid-washing and second heat-treatment.…”
Section: Active Site Formationo Ff E-n-hpc-ahe Lectrocatalystmentioning
confidence: 99%